A tunable dual-band asymmetric transmission metasurface with strong circular dichroism in the terahertz communication band. (June 2022) - Tao, Xiang; Qi, Limei; Fu, Tao; Wang, Bo; Uqaili, Junaid Ahmed; Lan, Chuwen
Highlights: A tunable terahertz dual-band graphene-based asymmetric transmission metasurface with strong circular dichroism is proposed. The metasurface can realize a dual-band asymmetric transmission effect only for a single-polarized linear wave. The coupled-mode theory is introduced to show the further physical mechanism of the tunable dual-band AT. The LCP and RCP waves can be detected by using the strong circular dichroism characteristics of the combined letter U. Abstract: We propose a tunable dual-band terahertz (THz) asymmetric transmission (AT) metasurface with strong circular dichroism (CD). The structure consists of two metal layers separated by a dielectric substrate with two strips of graphene sheets attached to one side of the dielectric substrate. By changing the chemical potential of the graphene, the tunable AT and the CD can be obtained for the two bands. The transmission coefficient T yx reduces from 0.768 to 0.34 for the first band, while it increases from 0.4 THz to 0.416 THz for the second band as the chemical potential μc increases from 0 eV to 1 eV. The CD also shows the tunable dual-band properties with peaks of 0.53 and 0.284, respectively. The coupled-mode theory is introduced to show the further physical mechanism of the tunable dual-band AT. As the dual-band AT metasurface shows strong CD, we can detect the right-handed circularly polarized (RCP) wave and left-handed circularly polarized (LCP) waves by demonstrating the field of the combination of the proposed metasurface with the mirrored one. These results would provide theoretical instructions in designing a tunable multi-band AT metasurface in the terahertz bands.